Development of a Microcontroller-Based Blind Smart Tool Design to Detect Obstacles Above and Below Automatically - Siti Nafisa Ifansyah; Nurmahni Harahap; Rizka Anggia Dinda (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
The senses that function to record the surroundings are the eyes, so that they can know the objects they see. In fact, normal eyes are not owned by all humans; there are also those who have had visual impairments since birth. Blind canes are commonly used by blind people to walk. But sometimes blind people still have difficulty when there are potholes, so it is not uncommon for blind people to fall into the hole. If there are obstacles in front of or around them and the road surface is uneven or has potholes, the blind will also have difficulty. Therefore, there is a great need for a walker in the form of a stick that is more adequate for blind people. Utilizing an ultrasonic sensor as a necessity is one of the designs of a blind cane. The function of the ultrasonic sensor is to detect holes, bumps, and obstacles that are above or below. The ultrasonic sensor works by using several main components, namely Arduino Uno as a controller, an MP3 module as an output, and a buzzer that will sound when detecting obstacles encountered. The purpose of this research is to find out about the development of a microcontroller-based smart stick (smart tool) to detect obstacles above and below automatically. The blind smart tool development process has gone through two stages of product revision. The results of the feasibility test in product revision test 2 are very feasible, with a total score of 30. The reading distance of the lower sensor is 60 cm, and the upper sensor is 100 cm.